Penyusunan Fungsi Produksi Tanaman Jagung: Ovigeria Subroto Sinaga - Ovigeria Subroto Sinaga (STIE Madani Balikpapan, 2021)
Corn is one of the agricultural products commonly handled by farmers. Currently corn is a commodity commodity that is being developed in Kutai Kartanegara Regency through the Corn Revolution movement. The corn revolution movement aims to increase the level of corn production in this district. One type of corn planted by farmers is sweet corn. This type of corn is preferred by consumers because it has good taste and can be used as raw material to make processed vegetables or directly consumed by boiling or baking. Farmers in planting corn certainly use various inputs or factors of production. One of the inputs that must be present is the use of corn seeds. Without the presence of corn seeds, the sweet corn cultivation activities could not be carried out. The use of inputs and outputs can be written into a production function. From this production function, we can find out how the position of using input in this sweet corn cultivation activity. It has reached the optimal point or not. In accordance with the theory of production, a good production function can describe